Distribution of Tuberculosis Cases Based on Case Detection and Treatment Outcomes in Morowali Regency, Central Sulawesi Province, 2022 - Mega Sabara; Aurel Amelia Putri Taoha (Journal of Health Science and Pharmacy, 2025)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and remains a significant public health problem in Central Sulawesi, Indonesia. The high rate of TB transmission is influenced by multiple factors, including unhealthy environmental conditions, high population density, and low levels of public awareness regarding TB prevention and treatment. Objectives: This study aims to describe the distribution of TB case detection and treatment in Morowali Regency, Central Sulawesi Province, during 2022. Methods: This study employed a descriptive quantitative design using secondary data obtained from the Central Sulawesi Provincial Health Profile. Data were analyzed using tables and graphical presentations to illustrate trends in TB case detection and treatment from 2020 to 2022. Results: The findings indicate that the number of TB cases detected in 2022 increased compared to the previous year; however, the achievement remained below the established targets. The COVID-19 pandemic, underreporting of cases by health facilities, and limitations in contact investigation activities were identified as the main barriers to optimal TB case detection. Conclusion: TB control efforts in Central Sulawesi continue to face substantial challenges. A comprehensive and collaborative approach involving multiple sectors and community participation is required to improve the coverage of TB case detection and treatment in a sustainable manner.